IbM KELOMPOK INDUSTRI RUMAH TANGGA KERAJINANALUMUNIUM DAN ALAT DAPUR DI KABUPATENBOYOLALI,MENINGKATKAN PENCETAKAN ALAT DAPUR SECARA MEKANIS - Achmad, Laila Faizah; Susanti, Margaretha Tuti; Kusumayanti, Heny; Paramita, Vita (Universitas Diponegoro, 2014)
Crafts copper and aluminum metal is well known as the only craft villages featured in Bambu Kuning Â District Boyolali which is the center of industry UKM need to be given guidance and training , especially for UKM that there is little need of such a helping hand for community service programs ( IbM ). IbM basic selection service programs to improve the quality and productivity of Â the aluminum craft in which the earlier process of making traditional , manually ( using hand -made) in order to become more mechanical craft aluminum kitchen equipment especially produced more precise form, include : Improvement of the manufacturing process of aluminum kitchen utensils mechanically, Design a simple hydraulic press tools according to their ability to operate and care for craftsmen improvement of more uniform product specifications in order to look more attractive.The method offered on IbM activities provide training and guidance to craftsmen on how to operate the hydraulic press tools properly and correct , also perfect the shape of the product so that the resulting shape kitchen tools more precise, more improved quality and can be sold at a higher price also to the wider marketing and export between islands . Plan that will be implemented to produce products in accordance with the Standard of food quality ( SII ) , starting from :1. Improvement of human resources with training and consultation on technology printing process2. Technology improvements equipment by designing a simple hydraulic press toolsTarget outcomes kitchen appliance is able to sell the product in accordance with the SII marketing broader, reaching levels of economical operation in the field of technology , management and promotion through the integration and synchronization of marketing flows from the point of production to the level of use of the product by the user or the user.